Pengaruh Cash Flow dan Debt terhadap Organizational Agility - Ana Marcal; Baldric Siregar; Frasto Biyanto; Miswanto Muslim; Hernandi J (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study's goal is to investigate how cash flow, debt, and profitability affect Indonesian public firms' adaptability. The percentage of R&D, training, and education expenses compared to revenue is another way to define agility. According to the Dynamic Capabilities Theory, an organization must be able to react effectively and swiftly to changes in its surroundings. According to the study's findings, which were based on secondary data gathered from 21 companies' annual reports between 2021 and 2023 and analyzed using multiple linear regressions, cash flow significantly and favorably influences agility, while leverage significantly and unfavorably affects agility. Unexpectedly, profitability even has a negative big impact on agility, in contrast to expectations. These findings also support that internal financial stability, such as cash flow management and debt structure, will be of a critical importance for mobilizing organizational agility. This research suggests the significance of balance between financial performance and long-term investment in human resources development and innovation in order to form an adaptive and competitive organization.